Travels in the World of the Old Testament. Studies Presented to Professor M. A. Beek on the Occasion of his 65th Birthday - Houwink ten Cate, Ph. H. J.; Heerma van Voss, M. S. H. G. (1974)
Gld. 70; u.a., L. van Reyendam-Beek, Biografie en bibliografie van M. A. Beek; С. J. Labuschagne, The našû - nadānu Formula and its Biblical Equivalent; L. Matouš, Der Assur-Tempel nach altassyrischen Urkunden aus Kültepe; W. H. Ph. Römer, Randbemerkungen zur Travestie von Deut. 22,5; A. van Selms, The Name Nebuchadnezzar.